COBRA. Season one [videorecording (DVD)] - Herbots, Hans, 1970-; Mackay, Al; Carlyle, Robert, 1961-; Hamilton, Victoria, 1971-; Dormer, Richard, 1969- (PBS, 2020)
It follows the Prime Minister and his titular committee, comprised of leading contingency planners and senior politicians, as they navigate the difficulties in overcoming a major national crisis.